Identity Construction of Women Online: The Case of My Stealthy Freedom - Shokoohi, Sadjad (My University, 2017)
Social Network Sites (SNS) have provided individuals with new ways of interaction, self-presentation, and identity construction through multimodal texts. Facebook as the most popular SNS today gives this opportunity to individuals in different ways, e.g. they can establish a personal Facebook page or a campaign as online activism. One of these campaign pages belongs to Iranian women who are against the obligatory hijab in Iran. As a way of protest, they perform self-presentations by means of multimodal texts; they depict themselves without hijab in public places and express their concern verbally. The aim of the current research is to study identity constructions of these women online by means of their multimodal self-presentation acts and the comments they receive from their Iranian compatriots. For the theoretical framework, the study adopts Goffman’s Self-Presentation Theory and his conceptualization of “gender” as a social construct. Besides, for the analysis of data different approaches of critical discourse analysis are employed. One of these approaches is Davies and Harré’s Positioning Theory. It is applied to investigate verbal self-presentations of the social actors and to study the way the commentators position the performances. The second approach is Van Leeuwen’s Visual Representation of Social Actors framework. It is applied to analyze visual self-presentations of the social actors. The results of the study suggest that Iranian women who perform self-presentation on the campaign page present themselves as against the obligatory hijab, and in ways to resist the imposed identities on them by the Islamic state. They show this resistance both verbally and visually. Moreover, the results show that most of the audience who comment on the social actors’ performances, accord “face” to them in the sense of Goffman. The co-construction, therefore, helps these women to maintain the presented selves.
Keywords: Identity construction online; self-presentation online; multimodal identity construction; Social Network Sites; gender; the hijab; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|